Geographic Inequalities in Accessibility of Essential Services - Vanda Almeida; Claire Hoffmann; Sebastian Königs; Ana Isabel Moreno-Monroy; Mauricio Salazar-Lozada; Javier Terrero-Dávila (Institute of Labor Economics (IZA), 2024)
People's ability to access essential services is key to their labour market and social inclusion. An important dimension of accessibility is physical accessibility, but little cross-country evidence exists on how close people live to the services facilities they need. This paper helps to address this gap, focusing on three types of essential services: Public Employment Services, primary schools and Early Childhood Education and Care. It collects and maps data on the location of these services for a selection of OECD countries and links them with data on population and transport infrastructure. This allows to compute travel times to the nearest service facility and to quantify disparities in accessibility at the regional level. The results highlight substantial inequalities in accessibility of essential services across and within countries. Although large parts of the population can easily reach these services in most countries, some people are relatively underserved. This is particularly the case in non-metropolitan and low-income regions. At the same time, accessibility seems to be associated with the potential demand for these services once accounting for other regional economic and demographic characteristics.
Keywords: H00; I24; J01; O18; R12; 330; geographic inequalities; geospatial disparities; service accessibility; social services; employment services